1989
DOI: 10.1042/bj2590477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II and of phorbol ester on protein kinase C activity and on prostacyclin production in cultured rat aortic smooth-muscle cells

Abstract: The role of the Ca2+-sensitive phospholipid-dependent protein kinase C (PKC) was studied in cultured rat aortic smooth-muscle cells, known to respond to angiotensin II (Ang II) by producing prostacyclin, determined by the release of 6-oxo-prostaglandin F1 alpha. PKC activity was measured in the cytosol and the solubilized membrane fraction after DEAE-cellulose chromatography using a linear NaCl gradient. Ang II stimulated the activity of PKC in the cytosolic and in the membrane fractions of aortic smooth-muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…PKC is known to activate MAPK presumably by directly phosphorylating Raf-1 (60). Since the present study showed that Ang II-induced MAPK activation was PI-PLC-dependent in VSMC and Ang II has been shown to stimulate PKC activity in VSMC through PI-PLC activation (14,61), Ang II could activate the Raf-1-MAPK system by activated PKC. Indeed, it has been reported that prolonged phorbol ester treatment significantly suppressed Ang II-induced Raf-1 and MAPK activation in cultured rat VSMC (20).…”
Section: Discussionmentioning
confidence: 88%
“…PKC is known to activate MAPK presumably by directly phosphorylating Raf-1 (60). Since the present study showed that Ang II-induced MAPK activation was PI-PLC-dependent in VSMC and Ang II has been shown to stimulate PKC activity in VSMC through PI-PLC activation (14,61), Ang II could activate the Raf-1-MAPK system by activated PKC. Indeed, it has been reported that prolonged phorbol ester treatment significantly suppressed Ang II-induced Raf-1 and MAPK activation in cultured rat VSMC (20).…”
Section: Discussionmentioning
confidence: 88%
“…As in mesangial cells, vasoconstrictor factors stimulate PG synthesis in cultured vascular smooth muscle cells, mainly prostaglandin E 2 and prostaglandin I 2 , which induce cell relaxation. 36,37 Only a few studies have been published assessing PG production in vascular tissue in cirrhosis. The urinary excretion of 2,3-dinor-6-keto-prostaglandin F 1␣ , a prostaglandin I 2 metabolite used to estimate the extrarenal production of prostaglandin I 2 , is increased in patients with cirrhosis, particularly in those with ascites, and correlates inversely with arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study (13) showed that activation of atypical PKC (aPKC) led to NF-jB activation and a decrease of PPARc expression. Considering the fact that various hormones, including insulin, angiotensin II, glucagons, parathyroid hormone, endothelin-1, thrombin, and vitamin D3, and high glucose concentration, activate c/nPKC (14)(15)(16)(17)(18)(19), evaluating the role of c/nPKC on gene expression in adipocyte may provide a new understanding of the regulation of insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%